Relationship Between Foveal Cone Specialization and Pit Morphology in Albinism - Wilk, Melissa A.; McAllister, John T.; Cooper, Robert F.; Dubis, Adam M.; Patitucci, Teresa N.; Summerfelt, Phyllis; Anderson, Jennifer L.; Stepien, Kimberly E.; Costakos, Deborah M.; Connor, Thomas B.; Wirostko, William J.; Chiang, Pei-Wen; et al. (Investigative ophthalmology & visual science, 2014)
Albinism is associated with disrupted foveal development, though intersubject variability is becoming appreciated. We sought to quantify this variability, and examine the relationship between foveal cone specialization and pit morphology in patients with a clinical diagnosis of albinism. We recruited 32 subjects with a clinical diagnosis of albinism. DNA was obtained from 25 subjects, and known albinism genes were analyzed for mutations. Relative inner and outer segment (IS and OS) lengthening (fovea-to-perifovea ratio) was determined from manually segmented spectral domain-optical coherence tomography (SD-OCT) B-scans. Foveal pit morphology was quantified for eight subjects from macular SD-OCT volumes. Ten subjects underwent imaging with adaptive optics scanning light ophthalmoscopy (AOSLO), and cone density was measured. We found mutations in 22 of 25 subjects, including five novel mutations. All subjects lacked complete excavation of inner retinal layers at the fovea, though four subjects had foveal pits with normal diameter and/or volume. Peak cone density and OS lengthening were variable and overlapped with that observed in normal controls. A fifth hyper-reflective band was observed in the outer retina on SD-OCT in the majority of the subjects with albinism. Foveal cone specialization and pit morphology vary greatly in albinism. Normal cone packing was observed in the absence of a foveal pit, suggesting a pit is not required for packing to occur. The degree to which retinal anatomy correlates with genotype or visual function remains unclear, and future examination of larger patient groups will provide important insight on this issue.